An Analysis of Internal Gravity Wave Tunnelling in a Stratified Region Along with Rotation - GANGAMANI, H. V.; NARGUND, ACHALA L; VENKATACHALAPPA, M. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The internal gravity wave tunnelling in presence of earths rotation is studied for different density barriers. An exponential approximation used reveals the existence of evanescence in the barrier region which signifies the trapping of wave energy in the tunnelling region. The Transmission coefficients are computed for different density barriers and the comparative study shows that across the locally mixed region the transmission is enhanced. The asymptotic analysis of the transmission co-efficient using the rotational parameter reveals the convergence and the graphs shows that the transmission decreases continuously and leads to the non-rotating case. The results are compared with the non-rotations case and we observe that the evanescence caused by the rotation makes the waves travel more along the horizontal direction than in the vertical direction.